2019
DOI: 10.14309/ajg.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor rs5186 Gene Variant Predicts Incident NAFLD and Associated Hypertension: Role of Dietary Fat-Induced Pro-Inflammatory Cell Activation

Abstract: OBJECTIVES: Hypertension has been linked to the presence and severity of nonalcoholic fatty liver disease (NAFLD) through unclear mechanisms. The gain-of-function rs5186 A1166C variant in angtiotensin receptor type 1 (AGTR1) gene has been linked to hypertension, cardiovascular disease and metabolic syndrome. We assessed the impact of AGTR1 A1166C variant on NAFLD incidence and severity and on glucose and lipid metabolism and explored the underlying mechanisms. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…In addition, rs2285666 SNP, has been recently related to a lower COVID-19 infection as well as case-fatality rate among Indian populations [19]. The rs5186 (C) allele in AGTR1 is associated with increased risk for essential hypertension [20,21]. Age and gender may also influence risk of AGTR1 SNPs and their role in hypertension and related disorders [22].…”
Section: Snps In Genes Of Renin-angiotensin System Included In the Studymentioning
confidence: 99%
“…In addition, rs2285666 SNP, has been recently related to a lower COVID-19 infection as well as case-fatality rate among Indian populations [19]. The rs5186 (C) allele in AGTR1 is associated with increased risk for essential hypertension [20,21]. Age and gender may also influence risk of AGTR1 SNPs and their role in hypertension and related disorders [22].…”
Section: Snps In Genes Of Renin-angiotensin System Included In the Studymentioning
confidence: 99%
“…Bioinformatic analysis revealed that the AGTR1 (angiotensin receptor type 1) gene, also connected with H. pylori infection and MetS [196,197], might be involved in several signaling pathways connected with the development of NAFLD [198]. In a recent prospective cohort study, the gain-of-function A1166C (rs5186) variant in the AGTR1 gene represented a strong predictor of incident NAFLD and related arterial hypertension [199]. Thus, despite the previous unsuccessful clinical trial of angiotensin receptor blockers in managing fibrosis in NAFLD patients [200], patients with the AGTR1 A1166C variant may exhibit a subtype of NAFLD that may benefit more from the personalized usage of angiotensin receptor blockers.…”
Section: Hypertension 5 H Pylori and Mets-related Nafld May Promote Arterial Hypertension By Increasing Vasoconstriction And Decreasing Vmentioning
confidence: 99%
“…In a recent prospective cohort study, the gain-of function A1166C (rs5186) variant in the AGTR1 gene represented a strong predictor for incident NAFLD and associated hypertension. In addition, polymorphism in AGTR1 may influence the risk of liver fibrosis in NAFLD [56].…”
Section: Genetic and Epigenetic Modificationsmentioning
confidence: 99%